UJI EFEKTIVITAS HIPERKOLESTEROLEMIA EKSTRAK ETANOL DAUN KECIPIR (Psophocarpus tetragonolobus L) PADA TIKUS PUTIH JANTAN (Rattus norvegicus) YANG DIINDUKSI KUNING TELUR BEBEK - sianipar, masria phetheresia; Syafitri, Anggun; Sembiring, Pintata (Jurnal Penelitian Farmasi Dan Herbal, 2024)
This study explored the effectiveness of winged leaf ethanol extract (Psophocarpus tetragonolobus L) in lowering cholesterol levels in male white rats (Rattus norvegicus) induced with duck egg yolk. An experimental method was used to eval__uate the impact of the extract on cholesterol levels, with the aim of providing an alternative treatment of hyperglycoleemia based on natural ingredients. The results show the significant potential of the extract. This research method uses an experimental approach with laboratory design. Male white rats (Rattus norvegicus) were divided into treatment and control groups. Winged leaf ethanol extract was administered to the treatment group, while the control group did not receive the treatment. Cholesterol level measurements were carried out after induction with duck egg yolk, to eval__uate the effectiveness of the extract in lowering cholesterol levels. The results showed that the administration of winged leaf ethanol extract significantly reduced total cholesterol, LDL, and triglyceride levels in induced male white rats. The group that received the highest dose of the extract showed the most favorable reduction in cholesterol levels, close to the effects of simvastatin. These findings indicate the potential of winged leaves as an alternative in the management of hypercholesterolemia. The conclusion of this study showed that winged leaf ethanol extract (Psophocarpus tetragonolobus L) was effective in lowering cholesterol levels in induced male white rats. A dose of 300 mg/kgBB has been shown to be the most effective. Recommendations for further research are to explore different dosage forms and extract concentrations, as well as conduct toxicity studies to ensure their safe use as a hypercholesterolemia therapy.